2010
DOI: 10.1007/s10566-010-9132-4
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Experiences and Juvenile Amenability: The Role of Trauma in Forensic Evaluations and Judicial Decision Making

Abstract: The legal files of 144 juveniles charged as adults in one Pennsylvania county were reviewed to investigate whether trauma-related information was included in evaluations of amenability to treatment and how that information related to legal decisions to keep youth in criminal court or decertify them to the juvenile system. Potentially traumatic experiences (PTEs) were noted in more than 71% of evaluations. Youth with any PTE documented were more likely to remain in criminal court, have more prior arrests, repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Traumatic experiences also predict marijuana use in juvenile offenders (Riggs Romaine, Goldstein, Hunt, & DeMatteo, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Traumatic experiences also predict marijuana use in juvenile offenders (Riggs Romaine, Goldstein, Hunt, & DeMatteo, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Victimization experiences, considered traumatic, have been associated with internalizing problems, such as depression and anxiety (Taylor and Weems 2009) and externalizing problems, for example, violent (Kimonis et al 2011), criminal and deviant behaviors (Kerig et al 2011; Mallie et al 2011; Riggs Romaine et al 2011). However, victimization (Margolin and Gordis 2000; Titus et al 2003) and other adverse experiences (Weems et al 2010) vary based on severity levels and severity of their impact on adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Although the youth may have personalized the trauma through guilt, blame, hopelessness, and other aspects of self-concept, his experiences are normalized as acceptance and validation is communicated throughout. Romaine and her colleagues found that although traumatic experiences were found in 71 % of youth cases in the juvenile system, only 6 % of evaluations specifi cally recommended treatment for these and associated issues (Romaine, Goldstein, Hunt, & DeMatteo, 2011 ). Juveniles with a history of trauma who are adjudicated for offending behaviors are more likely to have prior offending, reoffend, abuse substances, and have coexisting mental health disorders.…”
Section: Mode Deactivation Methodology and Traumamentioning
confidence: 99%